Application Of Business Model Canvas And Swot Analysis As A Tool For Formulating Strategic Steps For Palm Oil Mill Supplier Companies (Case PT. TCM) - Ernst Tunggul Pardomuan Siregar (Journal Research of Social Science, Economics, and Management, 2023)
Indonesia as the largest CPO producing country in the world has more than 850 palm oil mills that directly require a good maintenance system to ensure the smooth processing process. PT. TCM is one of the suppliers engaged in the palm oil industry. This paper discusses the marketing strategy used by PT. TCM, the potential and opportunities that arise to increase revenue and adding value to the company. The purpose of this paper is to provide input on changes in company strategy and can also be used by other players in the palm oil processing industry.